Keanekaragaman Spesies Amfibi (Ordo Anura) di Kawasan Cagar Alam Durian Luncuk II Provinsi Jambi - Koto, Ikhsan Nurdin; Aditiya, Randi; Nugraha, Anggit Prima (Konservasi Hayati, 2025)
Indonesia is home to 449 of the 7,757 Anura species that exist worldwide. An important component of the ecosystem, amphibians play a crucial role in maintaining environmental stability. Amphibians are quite vulnerable to changes in their environmental quality. The Durian Luncuk II Nature Reserve is an amphibian habitat in Batanghari Regency, Jambi Province. Covering 41.37 hectares of forest, this nature reserve was designated by the Minister of Forestry in 1997. Its lowland habitat and vegetation structure create an ideal environment for various amphibian species. This study aims to identify the amphibian species in the Duruan Luncuk II Nature Reserve and to determine the biological index. The research employs the Visual Encounter Survey (VES) method combined with the Line Transect system. The biological indices analyzed include the Diversity Index, Evenness Index, and species Richness Index. Data collection identified 11 amphibian species across four families. The Diversity Index was classified as moderate (2.1), while the Evenness Index indicated an almost uniform distribution (0.9). The species Richness Index was classified as low (2.8). Not all regions of CA Durian Luncuk II have been surveyed for this study. Therefore, a comprehensive survey in habitats that support amphibian encounters is still needed.